Psychological Health Of Elderly People In The Covid-19 Pandemic - Mierrina, Mierrina; Pradana, Charis Rizki (International Conference on Sustainable Health Promotion, 2021)
The pandemic has hit the world which has implications for all aspects of life, including the lives of the elderly. During the Covid-19 pandemic, this has also become an extraordinary adaptation process for other elderly people, which has an impact on their psychological health. This study aims to provide an overview of the psychological health of elderly people related to their psychological problems, during the Covid-19 pandemic. This is a descriptive study with quantitative methods, using a questionnaire as a data mining tool. Conducted on a sample of 96 elderly people in the age range 55-75 years. The results of the study in general that the elderly who experience psychological problems in general show that 15% are very suitable, 66% are suitable, 18% are not suitable and 1% are not very suitable. The problem with the largest percentage is the increase in negative emotions and death anxiety, which are 75% and 69%, respectively